2012
DOI: 10.1007/s10067-012-2016-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of new onset bilateral painful shoulder in patients with polymyalgia rheumatica and rheumatoid arthritis

Abstract: The aim of our study was to investigate by ultrasound (US) the anatomical structures affected during a new episode of bilateral painful shoulder in patients with polymyalgia rheumatica (PMR) and rheumatoid arthritis (RA) and to compare the findings between these two conditions. PMR and RA patients complaining of new onset bilateral painful shoulder were included. Subjects without any known rheumatic condition with a new onset unilateral painful shoulder were assessed as a control group. US evaluation includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 13 publications
1
34
0
3
Order By: Relevance
“…In contrast, no significant difference was detected in the distribution of biceps tenosynovitis among the study groups. Another study that looked at shoulder US findings in patients with PMR and RA confirmed that SAD bursitis was more specific to PMR (36). In this study, bilateral SAD bursitis was revealed in 37% of PMR patients, but only in 3% of patients with RA, while bilateral biceps tenosynovitis was present in 30% of PMR patients versus none of the RA controls.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…In contrast, no significant difference was detected in the distribution of biceps tenosynovitis among the study groups. Another study that looked at shoulder US findings in patients with PMR and RA confirmed that SAD bursitis was more specific to PMR (36). In this study, bilateral SAD bursitis was revealed in 37% of PMR patients, but only in 3% of patients with RA, while bilateral biceps tenosynovitis was present in 30% of PMR patients versus none of the RA controls.…”
supporting
confidence: 71%
“…Importantly, US in PMR has excellent reliability, with very high intra-observer (0.96) and inter-observer (0.99) intraclass correlation coefficients (11). The most frequent US abnormalities are usually detected at shoulder level and are represented by SAD bursitis and long head of biceps tendon tenosynovitis (12). According to a recent review, SAD bursitis is found in about 70-100% of patients with PMR, while the prevalence of long head of biceps tendon tenosynovitis hovers around 45-100% (13).…”
mentioning
confidence: 99%
“…The most frequent US abnormalities were detected at shoulder level and were represented by SAD bursitis and LTB tenosynovitis that have been reported in percentages ranging from 6.2%-100% (fig 1) [12][13]. However, the prevalence of SAD bursitis resulted higher compared to LBT tenosynovitis in the majority of the studies, suggesting this lesion as the inflammatory hallmark in PMR [13,[18][19][20]22,25,26].…”
Section: Ultrasonographic Findings In Pmr Patientsmentioning
confidence: 91%
“…As shown in table I, most of them were cross-sectional studies, were performed in Southern European countries (above all Italy) and described the main inflammatory US lesions at disease onset or during relapse. Except for the study of Zaccaria et al, they were conducted in small groups of PMR patients [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In terms of clinical assessment, when patients were investigated for the presence of symptoms, shoulder pain was the most frequent complain.…”
Section: Ultrasonographic Findings In Pmr Patientsmentioning
confidence: 99%
See 1 more Smart Citation